Comparison of Fuzzy-AHP and AHP in a spatial multi-criteria decision making model for urban land-use planning. (January 2015) - Mosadeghi, Razieh; Warnken, Jan; Tomlinson, Rodger; Mirfenderesk, Hamid
Highlights: Conventional AHP and Fuzzy AHP are compared in spatial MCDM land-use planning. The scale and scope of the decision-making are considered in comparative analysis. The spatial extents of the selected options are different in the two models. The AHP method is sufficient when identifying development options as focal points. When identifying spatial boundaries using two or more MCDM techniques would be ideal. Abstract: Modern planning theories encourage approaches that consider all stakeholders with a variety of discourse values to avoid political and manipulative decisions. In the last decade, application of quantitative approaches such as multi-criteria decision making techniques in land suitability procedures has increased, which allows handling heterogeneous data. The majority of these applications mainly used decision-making techniques to rank the priority of predefined management options or planning scenarios. The presented study, however, shows how spatial decision-making can be used not only to rank the priority of options and performing scenario analysis, but also to provide insight into the spatial extent of the alternatives. This is particularly helpful in situation where political transitions in regard to urban planning policies leave local decision-makers with considerable room for discretion. To achieve this, the study compares the results of two quantitative techniques (analytical hierarchy procedure (AHP) and Fuzzy AHP) in defining the extent of land-use zones at a large scale urban planning scenario. The presented approach also adds a new dimension to the comparative analysis of applying these techniques in urban planning by considering the scale and purpose of the decision-making. The result demonstrates that in the early stage of the planning process, when identifying development options as a focal point is required, simplified methods can be sufficient. In this situation, selecting more sophisticated techniques will not necessarily generate different outcomes. However, when planning requires identifying the spatial extent of the preferred development area, considering the intersection area suggested by both methods will be ideal.